TINJAUAN YURIDIS TERHADAP SANKSI PIDANA PENGGUNAAN TENAGA LISTRIK SECARA MELAWAN HUKUM DIKAITKAN DENGAN ASAS KEADILAN - Gustin, Darti Weni; Erdianto, Erdianto; Tiaraputri, Adi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Article 51 paragraf 3 of law number 30 of 2009 states that, “every personwho uses electric power which is not legally entitled to imprisonment for amaximum of 7 years and a maximum fine of 2.5000.000.000,00”. Based on theprinciple of justice, inessence it is abstrac and relative. In criminal law, especiallyin a criminal ase, justice is very difficult to create because there are two partieswith different interests who demand justice. The judge in case number24/Pid.Sus/2015/PN.Slw sentenced him to 3 months imprisonment and a fine of 3million rupiah. 1670/Pid.B/2016/PN.Mks and was sentenced to only 6 monthsimprisonment, and case number 222/Pid.Sus/2015/PN.Skh was sentenced to only6 months imprisonment. Meanwhile the electricity he stole was not only for theuse of his own household but also forthe benefit of his own personal business,which had harmed the state and also the community. So that from the result of thisdecision, the purpose of the punishment was dettering the perpetratorwas notachieved.The purpose of this study was criminal sanctions for electricity crime basedon the perspective of the principle of justice and to find out the ideal conceptrelated to electricity crime. This research is structured using a normative juridicalresearch type, namely research focused on examining the application of the rulesor norms in positive law. The approach used in this research namely literaturelaw research.The results of the research from the author are that In accordance with theprinciple of justice that the sentence that should be imposed must be inaccordance with the governing law, not with a judge’s decision which gives reliefvery far from the law that has been enacted. The judge’s decision that was handeddown was so low that it did not cause a deterrent effect on the perpetrator so thatis possible that this incident will happen again in the future. Ideal concept isachieved in determining the decision in accordance with the law against thejudge’s decision, and the criminal punishment imposed on the defendant shouldbe in accordance with the regulated law, namely law number 30 of 2009concerning electricity.Keywords: Electricity theft – justice – criminal sanction